Pengalaman Komunikasi Atlet E-Sport Mobile Legends Kota Bengkulu Dalam Upaya Memenangkan Permainan - Febriansyah Febriansyah; Vethy Octaviani; Salta Sari (Jurnal Multidisiplin Dehasen (MUDE), 2024)
Research purposes Esports as an online gaming competition has captured attention since the 1980s. Its rapid global growth has been fueled by technological advancements and the emergence of various tournaments that pique public interest. In Indonesia, esports is recognized as a national sport and receives support from laws and the government. The city of Bengkulu has also experienced significant growth in the gaming and esports industry, supported by the local government. Esports players in Bengkulu, particularly in Mobile Legends, have ventured into professional levels and can earn income from competitions at both local and national levels. Communication between players and fans, as well as a socialization venue, is an integral part of this esports phenomenon. Mobile Legends has become popular in esports competitions in Bengkulu. Matches involve ten players divided into two teams, and communication among team members is key to victory. This research aims to explore communication experiences within Mobile Legends esports teams in Bengkulu and how it affects team performance. Through qualitative research methods such as observation, interviews, and documentation, the study shows that effective communication and good teamwork play a significant role in achieving success in Mobile Legends esports. The research findings reveal that esports athletes often use group communication types, such as orientation, conflict, emergence, and reinforcement stages, which can strengthen team relationships and contribute to team success. In conclusion, this research emphasizes that effective communication, good conflict resolution, understanding of roles and strategies, and positive team support are key to success in esports, especially in Mobile Legends.